The Interactive Effect of Swimming Training and Curcumin on Bcl- 2 and Bax Gene Expression in the Rat Cardiac Tissue during the Withdrawal Period of Excessive Ethanol Consumption - Mona Abdolhamid Tehrani; Mohammad Ali Azarbayjani; Gholamreza Kaka (Islamic Azad University, 2017)
Introduction: Excessive consumption of ethanol can lead to development of apoptosis in cardiac tissue. Then, this study aimed to investigate anti-apoptotic effects of swimming training and curcumin during the withdrawal period of excessive ethanol consumption in rats. Methods: In an experimental study, 40 rats were selected and exposed to ethanol (25% w/v) every eight hours for four days by gavage. After 7 days of quitting ethanol consumption, they were placed in 5 groups of 8 each, including 1- control, 2-curcumin, 3-swimming training, 4-curcumin and swimming training, and 5- DMSO (dimethyl sulfoxide). Groups 3 and 4 performed five swimming training sessions per week for two weeks and groups 2 and 4 were received curcumin (50 mg/kg body weight) five times a week for two weeks by intraperitoneal injection. The two-way ANOVA was used for statistical analysis of data (P≤0.05). Results: Swimming training causes significant increase in Bcl-2 and significant decrease in Bax in the cardiac tissue of the rats received ethanol (P ≤ 0.05). Curcumin also significantly increased Bcl- 2 and decreased Bax (P ≤ 0.05). Curcumin and swimming training have interactive effects on the reduction of Bax in the cardiac tissue of rats (P ≤ 0.05). However, the concurrence of these two factors did not have a significant interactive effect on Bcl-2 elevation and Bax/Bcl- 2 gene expression regulation (P ≥ 0.05). Conclusion: Based on the results, swimming training and curcumin consumption alone had a significant effect on reducing the ethanol-induced apoptosis in cardiac tissues of the rats during the withdrawal period of excessive ethanol use. Furthermore, results showed that swimming training with curcumin consumption had a significant interactive effect on reducing Bax gene expression. However the interactive effect of the combination of training and curcumin on Bcl- 2 and Bax/Bcl- 2 ratio was not significant, but it is more effective than the effect of each intervention alone. Consequently, it seems that the combination of swimming training and curcumin may be used during the withdrawal period of excessive ethanol consumption to modulate apoptotic process.